"Such a section as never was put together before":: Logan, Dawson, Lyell, and mid-Nineteenth-Century measurements of the Pennsylvanian Joggins section of Nova Scotia - Rygel, Michael; Shipley, Brian (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2005)
Abstract William Edmond Logan assumed his duties as the first head of the Geological Survey of Canada in June 1843. Two previously overlooked field notebooks provide new insight into his first field project that summer: measurement of the "Joggins section," a classic Carboniferous locality in Nova Scotia. Inspired by reports of 40-foot-tall fossil trees, Logan spent five days measuring 14 570 feet 11 inches of strata exposed along die shore of the Bay of Fundy. Widely regarded as a meticulous, bed-by-bed measured section, closer examination reveals that many thickness values were calculated using paced distances. Realizing that his measured section was too detailed for scientific journals of the day, Logan published his work in a relatively obscure government publication where it went largely unnoticed for nearly a decade. Unaware of Logan's measured section, John William Dawson and Charles Lyell visited Joggins in 1852 and measured the section for themselves. Dawson later stated that the two sections contain only minor differences, but careful comparison shows that they have radically different descriptions and measurements for even the most distinctive beds. Dawson disguised these discrepancies in post-1855 editions of his book Acadian Geology by rewriting much of the measured section and abandoning many of his own observations. Although over 200 subsequent Joggins studies build upon these measured sections, the present study represents the first detailed examination of the two historical sections and reveals previously unknown discrepancies between two of the most important early geologic studies undertaken in Nova Scotia.